Disclosure of Risk Management Processes at The Best Banks In Indonesia - Bahiyyah, Khariidatul; Kurniawati, Yuyun; Romdoni, Nijar Kurnia; Sutarsa, Monika; Sofyan, Harnavela; Usmar, Andi (International Journal of Economics Development Research (IJEDR), 2025)
This study analyzes the disclosure of the procedure for risk management conducted by the bank that won the best title in Indonesia in 2023 with OJK's provisions regulations on the implementation of risk management for commercial banks. This study uses content analysis by determining the level of breadth of disclosure, namely full, undisclosed, and vaguely disclosed. The review is carried out on the annual report of each bank. The results of the study found that the bank that excelled in full disclosure was BBRI with the disclosure of 6 categories out of the supposed 7 categories in the disclosure of the uncertainty management process for market uncertainty. The disclosure of the credit risk management process, BBNI is superior to 5 categories than it should be 7 categories. Meanwhile, in liquidity risk, BBNI's disclosure is the lowest from other banks, which is only 4 categories out of 7 categories. The research conducted resulted in new knowledge that although it won the title of the best bank in Indonesia, in the process of disclosure of risk management, not all categories set by the OJK are met.